A near-infrared fluoride sensor based on a substituted naphthalenediimide–anthraquinone conjugate. Issue 33 (12th August 2015) - Bobe, Sharad R.; Bhosale, Sidhanath V.; Jones, Lathe; Puyad, Avinash L.; Raynor, Aaron M.; Bhosale, Sheshanath V.
Graphical abstract: Highlights: A donor-acceptor based NIR sensor. Synthesis of a novel core-substituted naphthalene diimide with anthraquinone. A fluorescent, neutral and selective and sensitive colorimetric sensor for the fluoride ion through effect of intramolecular charge transfer upon fluoride binding for the first time. Abstract: The synthesis and characterization of a highly selective fluoride receptor based on a naphthalene diimide substituted with an anthraquinone (NDI-AQ ) moiety is described. In CHCl3, the receptor was shown to be highly selective for fluoride ( K a ∼10 3  M −1 ) over other anions (AcO −, HSO4 −, Br −, Cl −, I −, ClO4 −, H2 PO4 −, and NO3 − ) with pronounced changes in absorption characteristics, that is, red-shift of the absorption band to 790 nm (NIR). The visual color change, NIR shift in absorption, emission spectroscopy, and electrochemistry thus support an intramolecular charge transfer (ICT) effect upon fluoride binding to theNDI-AQ receptor.